When learned indexes meet LSM-tree based systems: an empirical evaluation - Chen, Mengshi (Nanyang Technological University, 2024)
The learned indexes have demonstrated significant performance enhancements through a computational methodology, as opposed to the traditional indexes relying on comparisons. Recent studies shed light on the benefits of learned indexes when they are embedded into LSM-tree-based storage systems, with a case study on a simple baseline learned index. Nevertheless, it remains uncertain whether the system can capitalize on the recent advancements in learned indexes research.